2012
DOI: 10.1002/prop.201200080
|View full text |Cite
|
Sign up to set email alerts
|

A Boseā€Einstein condensate in a š’«š’Æ symmetric double well

Abstract: The existence of š’«š’Æ symmetric wave functions describing Boseā€Einstein condensates in a oneā€dimensional and a fully threeā€dimensional doubleā€well setup is investigated theoretically. When particles are removed from one well and coherently injected into the other the external potential is š’«š’Æ symmetric. We solve the underlying Grossā€Pitaevskii equation by way of the timeā€dependent variational principle (TDVP) and show that the š’«š’Æ symmetry of the external potential is preserved by both the wave functions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(125 citation statements)
references
References 35 publications
4
121
0
Order By: Relevance
“…Previous works showed that the nonanalytic nonlinearity of the GPE, which is proportional to the square modulus of the wave function |Ļˆ| 2 , is responsible for the change in the number of solutions at the bifurcation points [28,35,36].…”
Section: Analytic Continuationmentioning
confidence: 99%
“…Previous works showed that the nonanalytic nonlinearity of the GPE, which is proportional to the square modulus of the wave function |Ļˆ| 2 , is responsible for the change in the number of solutions at the bifurcation points [28,35,36].…”
Section: Analytic Continuationmentioning
confidence: 99%
“…Figure 4a shows Fig. 4 (a) Energy spectrum E (2) 0 of the only existing state Ļ† (2) 0 in the system described by the potential V 2 for removed ground state. For comparison the energy E (1) 1 of the original system is also shown.…”
Section: Removal Of Pt -Symmetric Statesmentioning
confidence: 99%
“…The only existing state is the former excited state, which is the ground state of the new system, and hence is labelled Ļ† (2) 0 . Its energy must be positive since it must be above that …”
Section: Removal Of Pt -Symmetric Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential is extended with asymmetric imaginary parts, representing a particle drain in one well and a particle source in the other. Theoretical investigations revealed that this PT -symmetric system has observable eigenstates [19][20][21][26][27][28][29][30][31]. However, an experimental confirmation of these results cannot be made as long as there is no way to realize a non-Hermitian potential.…”
Section: Introductionmentioning
confidence: 99%